SiO2 / Ica-PDA-FA multifunctional nanoparticles as well as preparation method and application thereof
Through the application of SiO2/Ica-PDA-FA nanoparticles in tumor cells, the problems of poor water solubility and low bioavailability of icaridin were solved, and the dual effects of low-temperature photothermal therapy and drug therapy were achieved, which significantly inhibited the colon The proliferation and apoptosis of cancer cells reduce damage to surrounding tissues.
Patent Information
- Application Number
- CN202411783996.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The poor water solubility and low bioavailability of icimerin limit its widespread use in clinical applications. Traditional low-temperature photothermal therapy has problems with heat resistance to tumor cells and damage to surrounding normal cells, and the high expression of HSP90 reduces the therapeutic effect. .
Develop SiO2/Ica-PDA-FA nanoparticles, using SiO2 as a carrier to load icaridin, surface modification of polydopamine and folic acid, promote Icaritin release through acidic and glutathione environments, inhibit HSP90 expression, and under near-infrared irradiation Achieve the dual anti-tumor effects of low-temperature photothermal therapy and drug therapy.
Improves the water solubility and drug release efficiency of Icaritin, enhances the targeting and anti-tumor effect on tumor cells, reduces damage to surrounding tissues, realizes the stability of low-temperature photothermal therapy and the effective dose of drugs, significantly inhibits Proliferation and apoptosis of colon cancer cells.
Smart Images

Figure CN119258239A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of nanomaterial anti-tumor drugs, and in particular, relates to a SiO2 / Ica-PDA-FA multifunctional nanoparticle and a preparation method and application thereof. Background Art
[0002] Cancer is a major issue threatening human health worldwide. The incidence of colorectal cancer ranks third among all cancers, second only to breast cancer and lung cancer. In 2020, more than 1.93 million people were diagnosed with colorectal cancer worldwide, accounting for 9.7% of the world's newly diagnosed cancers, and the incidence and mortality rates are also increasing year by year. The treatment of colorectal cancer is mainly comprehensive treatment, and commonly used methods include surgery, radiotherapy, chemotherapy, immunotherapy and targeted therapy. Although most colorectal cancer lesions can be removed surgically, many patients will experience local recurrence or metastasis within several years after surgery. In addition, some patients are already in the advanced stage when diagnosed, missing the time window for surgical resection. Therefore, the current treatment methods have limited impact on the cure rate and long-term survival rate of colorectal cancer. In recent years, in addition to traditional chemotherapy drugs, molecular targeted drugs and immunosuppressants have also been used to treat colorectal cancer. Although these drugs have achieved good results in some patients, they still have many toxic side effects and some patients have poor treatment response. Therefore, it is still of great significance to find new safe and effective therapeutic drugs with less toxic side effects.
[0003] Icaritin is a derivative of the flavonoid monomer icariin extracted from the plant Epimedium. Studies have shown that it has a wide range of biological activities, including anti-tumor, reproductive enhancement, bone and joint protection, cardiovascular protection, immune enhancement, anti-aging, anti-inflammatory, radiation protection and other drug effects. Although Icaritin has multiple biological activities, its poor water solubility and low bioavailability limit its widespread clinical application.
[0004] In recent years, multifunctional nano-delivery systems that integrate one or more of the treatment methods of photothermal therapy (PTT), photodynamic therapy, chemotherapy or sonodynamic therapy have gradually attracted the attention of researchers and have gradually become a hot field for anti-tumor clinical research and application. The nonspecific heating and thermal diffusion induced by traditional PTT cause the temperature of tumor tissue to be higher than 50°C, which not only increases the risk of tumor recurrence and metastasis, but also damages the surrounding normal cells and tissues. In addition, studies have shown that the high expression of HSP90 in tumor cells increases the heat resistance limit of cells, thereby reducing the PTT effect, while inhibiting the expression level of HSP90 can synergistically promote the anti-tumor effect of chemotherapy, radiotherapy and other means. In addition, HSP90 can play an important protective role in cells as a molecular chaperone protein. When cells are exposed to extreme temperatures, hypoxia or drugs and other stress conditions, heat shock proteins help maintain protein folding and other natural structural functions. Therefore, reducing the high temperature tolerance of tumor cells and using low-temperature photothermal therapy (LTPTT, temperature below 45°C) to ablate tumors is a hot topic and cutting-edge content in current photothermal therapy research. Summary of the invention
[0005] The purpose of the present invention is mainly to develop a SiO2 / Ica-PDA-FA nanoparticle with a synergistic effect of low-temperature photothermal therapy and its preparation method and application in view of the problems of poor water solubility and low bioavailability of icariin. The nanoparticle uses SiO2 as a carrier, and Icaritin is loaded on the carrier to improve the dispersibility of Icaritin in aqueous solution and give full play to its pharmacological effect. At the same time, PDA and FA are modified on the surface, and FA actively targets tumor tissues, promotes the release of Icaritin in the acidic environment of cells and high concentration of glutathione, thereby inhibiting the expression of HSP90, overcoming the heat resistance of tumor cells, and realizing the dual anti-tumor effects of low-temperature photothermal therapy and Icaritin drug therapy under near-infrared irradiation.
[0006] The main technical solutions of the present invention are as follows:
[0007] In a first aspect, the present invention provides a SiO2 / Ica-PDA-FA multifunctional nanoparticle, wherein the multifunctional nanoparticle is a core-shell structure, with silica as a carrier, and the surface of the silica is loaded with icariin and modified with polydopamine and folic acid.
[0008] As a possible design, the silica is organic mesoporous silica.
[0009] In a second aspect, the present invention provides a method for preparing SiO2 / Ica-PDA-FA multifunctional nanoparticles, comprising:
[0010] dispersing silicon dioxide in a dispersion liquid to form a suspension;
[0011] Icariin is added to the suspension, and after the reaction is completed at room temperature, the suspension is stirred and centrifuged to obtain SiO2 / Ica nanoparticles; the mass ratio of silicon dioxide to icariin is 4-6:1;
[0012] Dopamine hydrochloride is dispersed in a solvent to form a dopamine hydrochloride solution;
[0013] The dopamine hydrochloride solution and SiO2 / Ica nanoparticles were mixed and reacted at room temperature, and then centrifuged and dried to obtain SiO2 / Ica-PDA nanoparticles with a core-shell structure; the mass ratio of dopamine hydrochloride to SiO2 / Ica nanoparticles was 0.8-1.2:1;
[0014] dissolving NH2-PEG-FA in a buffer solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to obtain an NH2-PEG-FA solution;
[0015] SiO2 / Ica-PDA nanoparticles are dispersed in the dispersion to form a SiO2 / Ica-PDA suspension;
[0016] The NH2-PEG-FA solution is added dropwise to the SiO2 / Ica-PDA suspension for reaction, and after the reaction is completed, the SiO2 / Ica-PDA-FA multifunctional nanoparticles are obtained by centrifugation and washing;
[0017] The mass ratio of the NH2-PEG-FA, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide and SiO2 / Ica-PDA nanoparticles is 0.7-1.2:1.8-2.2:0.8-1.5:5.5-6.3.
[0018] As a possible design, the NH2-PEG-FA is prepared by the following steps:
[0019] dissolving the NH2-PEG-NH2 polymer in a NaHCO3 solution to form an NH2-PEG-NH2 solution;
[0020] (Boc)2O is dissolved in dioxane solution to form (Boc)2O solution; NH2-PEG-NH2 polymer, NaHCO 3、 The mass ratio of (Boc)2O and dioxane is: 1.5~2.2:0.253:0.206:62.04;
[0021] Add (Boc)2O solution to NH2-PEG-NH2 solution under ice bath condition, react at room temperature after adding, adjust pH value to 7-8 after reaction, extract after rotary evaporation to obtain BOC-PEG-NH2; add solvent to BOC-PEG-NH2 to obtain BOC-PEG-NH2 solution;
[0022] Dissolving folic acid in a buffer solution containing 1-ethyl-(3-dimethylaminopropylcarbodiimide) and N-hydroxysuccinimide to form a folic acid solution; the mass ratio of folic acid, 1-ethyl-(3-dimethylaminopropylcarbodiimide) and N-hydroxysuccinimide is 0.8-1.2:2:1.2;
[0023] The BOC-PEG-NH2 solution was added dropwise to the folic acid solution for reaction at room temperature. After the reaction was completed, BOC-PEG-FA was obtained by rotary evaporation.
[0024] BOC-PEG-FA was dissolved in anhydrous dichloromethane, and trifluoroacetic acid was added to react at room temperature. After the reaction was completed, the NH2-PEG-FA was obtained by rotary evaporation, ether precipitation and vacuum drying; the mass ratio of BOC-PEG-FA, anhydrous dichloromethane and trifluoroacetic acid was 0.8~1.3:13.25:5.3725.
[0025] As a possible design, the silicon dioxide is prepared by the following steps:
[0026] dissolving hexadecyltrimethylammonium bromide in a solvent containing aqueous ammonia to form a mixed solution;
[0027] The mixed solution is added into a mixed solution formed by ethyl orthosilicate and bis-[3-(triethoxy)silylpropyl]tetrasulfide, and after the reaction is completed, a white precipitate is obtained by centrifugation;
[0028] The mass ratio of hexadecyltrimethylammonium bromide to ethyl orthosilicate is 20~35mg:1.5~2.0ml;
[0029] The volume ratio of ethyl orthosilicate to bis-[3-(triethoxy)silylpropyl]tetrasulfide is 0.7~1.2:1.
[0030] As a possible design, the white precipitate is purified by acidic ethanol reflux method.
[0031] As a possible design, the white precipitate is dispersed in an acidic ethanol solution and refluxed for 7 to 9 hours.
[0032] As a possible design, the temperature of the mixed solution during the formation process is 75-82°C.
[0033] Beneficial effects of the present invention:
[0034] 1. SiO2 / ICA nanoparticles are evenly distributed in spherical shape and have good dispersibility. After being coated with PDA, SiO2 / ICA-PDA nanoparticles have a distinct core-shell structure. The hydrated particle size of SiO2 / ICA nanoparticles is about 60nm, with a negative charge of -2mV. The particle size of SiO2 / Ica-PDA is about 115nm, with a potential of about -18mV. The particle size of SiO2 / Ica-PDA-FA is about 120nm, with a potential of -5mV, which is more conducive to cell phagocytosis.
[0035] 2. The SiO2 / Ica-PDA-FA nanoparticles prepared by the present invention have a good photothermal effect under NIR irradiation. After repeated NIR irradiation for 4 times, the maximum temperature of the SiO2 / Ica-PDA-FA nanoparticles did not change, and the photothermal stability was good.
[0036] 3. The release rate of Icaritin from the SiO2 / Ica-PDA-FA nanoparticles prepared by the present invention was 49% under dual stimulation of acidity at pH 5.5 and GSH (glutathione). On this basis, the release rate of Icaritin after NIR treatment was 70%, indicating that the nanoparticles can quickly respond to the tumor cell microenvironment under NIR irradiation and increase the effective dose of intracellular drugs.
[0037] 4. The SiO2 / Ica-PDA-FA nanoparticles prepared by the present invention have a strong effect of inhibiting the proliferation of colon cancer cells and have good penetration ability in tumor spheres, so they can be used in drugs for treating tumors.
[0038] 5. The SiO2 / Ica-PDA-FA nanoparticles prepared by the present invention have good biosafety and can significantly kill tumor cells under near-infrared lasers with a wavelength of 808nm. The present invention can make SiO2 / Ica-PDA-FA nanomaterials slowly release drugs at the tumor site, PDA encapsulation can respond to NIR to increase temperature, FA binds to folate receptors highly expressed on the surface of tumor cells, and actively and specifically targets tumor cells to increase the enrichment of ICA in tumor tissues. On this basis, ICA causes tumor apoptosis and reduces the expression of HSP90, improving the photothermal treatment effect under NIR irradiation conditions and reducing damage to surrounding tumor tissues. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0040] Figure 1 This is a diagram showing the preparation and characterization results of SiO2 / Ica-PDA-FA nanoparticles prepared in Example 1 of the present invention;
[0041] Figure 2 1 is a photothermal effect and stability result diagram of SiO2 / Ica-PDA-FA nanoparticles prepared in Example 1 of the present invention;
[0042] Figure 3 is a graph showing the drug release performance of SiO2 / Ica-PDA-FA nanoparticles prepared in Example 1 of the present invention;
[0043] Figure 4 are the uptake fluorescence (a) and flow cytometry (b) images of SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA nanoparticles in Example 1 of the present invention;
[0044] Figure 5 is a flow cytometric graph (a) of the inhibition rate of various nanoparticles on HCT116 cells before and after NIR irradiation and the induction of apoptosis (b) in Example 1 of the present invention;
[0045] Figure 6 It is the fluorescent images of the dead and alive colon cancer cells treated with various nanomedicines before and after NIR irradiation;
[0046] Figure 7 is a graph showing the effect of different NIR irradiation times and the effect of SiO2 / Ica-PDA-FA nanoparticles obtained in Example 1 on the penetration of colon cancer;
[0047] Figure 8 The distribution diagram of SiO2 / Ica-PDA-FA nanoparticles prepared in Example 1 of the present invention in different tissues of mice and their in vivo retention time;
[0048] Fig. 9 These are the H&E staining and biochemical detection images of important organs after various nanoparticle treatments;
[0049] Fig.10 is the photothermal effect diagram of SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA nanoparticles at different NIR irradiation times;
[0050] Fig.11 This is a graph showing the results of various nanoparticles treating subcutaneous tumors in mice. DETAILED DESCRIPTION
[0051] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0052] In the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0053] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0054] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as µg, mg, g, kg, etc.
[0055] Example 1
[0056] (1) Preparation of MSNs (organic mesoporous silica):
[0057] First, 25 mg of hexadecyltrimethylammonium bromide was dissolved in a mixture containing 110 mL of deionized water, 10 mL of anhydrous ethanol and 0.875 mL of ammonia (concentration 2M) at 80 °C, and then 1.75 mL of tetraethyl orthosilicate (TEOS) and 1.75 mL of bis-[3-(triethoxy)silylpropyl]tetrasulfide (BTSPD) were added under stirring, TEOS:BTSPD (volume ratio) = 1:1, and stirring was continued for 5 h. After cooling to room temperature, the white precipitate was collected by centrifugation for 20 min (speed of 18000 rpm) and washed with anhydrous ethanol and deionized water three times respectively. The surfactant in the pores of MSNs was removed by acidic ethanol reflux method, that is, the washed nanocarriers were dispersed in an acidic ethanol solution containing 50 mL of ethanol and 1 mL of hydrochloric acid (37%) and refluxed for 8 h to remove the template to obtain SiO2 nanocarriers.
[0058] (2) MSNs nanocarrier loaded with Icaritin:
[0059] 10 mg SiO 2`The nanocarriers were dispersed in 10 mL of ethanol solution, and then 2 mg of Icaritin was added to the suspension and stirred at room temperature for 24 h. After stirring, the nanoparticles carrying Icaritin were collected by centrifugation and washed three times with ethanol solution to remove excess Icaritin. After freeze-drying, they were named SiO2 / Ica nanoparticles.
[0060] (3) PDA encapsulated SiO2 / Ica nanoparticles PDA:
[0061] The specific steps of PDA (polydopamine) encapsulation of SiO2 / Ica nanoparticles are as follows: 100 mg of dopamine hydrochloride was dissolved in 100 mL of Tris-HCl buffer (10 mM, pH 8.5), and then 100 mg of SiO2 / Ica nanoparticles were dispersed in dopamine-Tris buffer and reacted at room temperature for 12 h. PDA silica nanoparticles with core-shell structure were obtained by centrifugation and washed 3 times with deionized water, and named SiO2 / Ica-PDA nanoparticles after freeze-drying.
[0062] (4) FA modified on the surface of SiO2 / Ica-PDA nanoparticles:
[0063] Dissolve 2 g of NH2-PEG-NH2 polymer in 30 mL of 0.1 mol / L NaHCO3 solution, and dissolve 0.206 g of (Boc)2O in 60 mL of dioxane solution. Add the (Boc)2O dioxane solution dropwise to the NaHCO3 solution containing NH2-PEG-NH2 under ice bath conditions, and stir the reaction at room temperature for 18 h. After the reaction is completed, add 2 M HCl to adjust the pH to 7-8, remove the solvent by rotary evaporation, and extract with dichloromethane 5 times. After filtering and rotary evaporation to remove the solvent, a light yellow oily substance is obtained, which is the compound BOC-PEG-NH2, which is dissolved in 10 mL of deionized water for later use. Then, 1 g of FA (folic acid) was dissolved in 100 mL of PBS solution containing 2 g of 1-ethyl-(3-dimethylaminopropylcarbodiimide) (EDC) and 1.2 g of N-hydroxysuccinimide (NHS), and stirred at room temperature for 4 h. The prepared BOC-PEG-NH2 solution was added dropwise to the above FA solution and stirred at room temperature for 24 h. After stirring, dichloromethane was added for extraction 3 times, and the yellow oily compound was obtained by rotary evaporation to remove the solvent, which was BOC-PEG-FA. 1 g of BOC-PEG-FA polymer was dissolved in 10 mL of anhydrous dichloromethane, and then 3.5 mL of trifluoroacetic acid was slowly added dropwise at room temperature and stirred for 2 h. After the reaction was completed, the compound NH2-PEG-FA was obtained after rotary evaporation, ether precipitation and vacuum drying. (4) Dissolve 1 mg of NH2-PEG-FA in 10 mL of PBS solution containing 2 mg of EDC and 1.2 mg of NHS, and stir at room temperature for 4 h. Disperse SiO2 / Ica-PDA nanoparticles in 10 mL of deionized water, and slowly add the above-obtained NH2-PEG-FA solution to the suspension, and then stir at room temperature for 24 h. After stirring, collect by centrifugation, and wash three times with PBS to obtain SiO2 / Ica-PDA-FA nanoparticles. Figure 1 Wherein ab is a schematic diagram of the preparation of SiO2 / Ica-PDA-FA nanoparticles and a flow chart of the preparation of intermediate products, specifically: (a) schematic diagram of the preparation process; (b) synthetic route of NH2-PEG-FA compound.
[0064] 1. The nanoparticles involved in Example 1 were characterized as follows:
[0065] (1) Since SiO2 / Ica-PDA-FA is an insoluble solid and cannot be characterized by nuclear magnetic resonance, the nuclear magnetic resonance characterization of the NH2-PEG-FA compound in this application is as follows: the NH2-PEG-FA polymer sample is dissolved in DMSO-d6 (Chinese name: dimethyl sulfoxide-d6), tetramethylsilane is used as the internal standard, and the sample is detected by a nuclear magnetic resonance instrument at room temperature to obtain a nuclear magnetic resonance hydrogen spectrum (1H-NMR). Figure 1 c is NH2-PEG-FA dissolved in DMSO-d6 and characterized by NMR. 1 H-NMR (DMSO-d6, ppm,δ): 8.61(-N=C H -C=N-), 7.53(C6 H 5CO), 6.63(NHC6 H 5), 4.42(≡CC H 2-NH-), 3.5 (-NH-CH2-C H 2-O-), indicating that the polymer NH2-PEG-FA was successfully synthesized.
[0066] (2) Particle size and potential characterization: The prepared nanoparticles SiO2 / Ica, SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA were diluted with deionized water to a suspension concentration of 0.5 mg / mL. The particle size and Zeta potential of the three nanoparticles were tested using a dynamic light scattering (DLS) particle size analyzer at 25°C. Figure 1 hi is the particle size and potential of various nanoparticles, i.e., the particle size distribution and Zeta potential changes of SiO2 / Ica, SiO2 / Ica-PDA, and SiO2 / Ica-PDA-FA. The hydrated particle size of SiO2 / Ica nanoparticles is about 60 nm, the particle size of SiO2 / Ica-PDA is about 115 nm, and when the surface of SiO2 / Ica-PDA is modified with the targeting group FA, the particle size is about 120 nm. The potential of SiO2 nanocarrier is -11mV, and the potential of nanoparticles SiO2 / Ica after loading Icaritin increases to -2 mV, indicating that Icaritin is successfully loaded on SiO2 nanocarrier. Coating PDA and grafting FA also affect the surface potential of nanoparticles. Compared with SiO2 / Ica-PDA, the final SiO2 / Ica-PDA-FA nanoparticles have a potential of -5 mV, which is more conducive to cell phagocytosis.
[0067] (3) Characterization of drug loading: Icaritin of different concentrations was dissolved in DMSO solution and its absorbance at 375 nm was measured, and a standard curve was prepared. Weigh 5 mg of lyophilized nanoparticles carrying Icaritin, disperse it in a DMSO / water mixture, adjust the pH to 5 with 0.01 M dilute hydrochloric acid, let it stand for stratification, take the DMSO phase, extract it 4 times continuously, and measure the absorbance at 375 nm. Calculate the drug loading of Icaritin based on the standard curve. Figure 1 Figure g in the middle is the UV-vis spectra of iO2, Icaritin and SiO2 / Ica. It is known that Icaritin has obvious characteristic absorption peaks at 273 nm and 375 nm. Using the characteristic peak absorption properties of Icaritin, when Icaritin is loaded into SiO2 nanocarriers, SiO2 / Ica nanoparticles still have characteristic absorption peaks at 273 nm and 375 nm. This result shows that Icaritin is successfully loaded into SiO2 nanocarriers.
[0068] (5) Surface morphology characterization: 0.5 mg of SiO2 / Ica and SiO2 / Ica-PDA nanoparticles were dispersed in 1 mL of deionized water and then dropped onto a tray. After the water evaporated, they were spray-coated with gold and the microscopic morphology of the nanoparticles was observed using a scanning electron microscope. Figure 1 Figure d in the middle shows the morphology of SiO2 / Ica and SiO2 / Ica-PDA nanoparticles by SEM. It can be seen that the morphology of SiO2 / Ica nanoparticles is uniformly distributed spherical and has good dispersion. After coating with PDA, SiO2 / Ica-PDA nanoparticles still maintain spherical shape, indicating that the coating process of PDA did not destroy the basic morphology of SiO2 / Ica.
[0069] (6) Transmission electron microscopy (TEM) was used to characterize the structure of SiO2 / Ica and SiO2 / Ica-PDA nanoparticles. SiO2 / Ica and SiO2 / Ica-PDA nanoparticles with a concentration of 0.5 mg / mL were dropped onto a 200-mesh copper grid. After the water was allowed to evaporate, the microstructure of the nanoparticles was observed using TEM, and the elemental composition of the nanoparticles was analyzed using TEM mapping. Figure 1 Figure e in the middle shows the morphology of the nanoparticles observed by TEM. The SiO2 / Ica nanoparticles are irregularly and evenly dispersed spheres; the SiO2 / Ica-PDA nanoparticles have obvious apertures on the outer layer and present a regular core-shell structure, which once again proves that PDA is successfully coated on the surface of the SiO2 / Ica nanocomposite. Figure 1Figure f in the middle shows the element types of SiO2 / Ica and SiO2 / Ica-PDA through TEM element mapping analysis. Figure f shows that SiO2 / Ica nanoparticles are irregularly and evenly dispersed spheres, and the three elements Si, S and O are evenly distributed on SiO2 / Ica nanoparticles. Compared with SiO2 / Ica nanoparticles, SiO2 / Ica-PDA nanoparticles contain four elements Si, S, O and N. The appearance of N element indicates that PDA is successfully coated on the surface of SiO2 / Ica nanoparticles.
[0070] (7) Characterization of photothermal effect: In order to verify the photothermal effect of SiO2 / Ica-PDA-FA nanoparticles, SiO2 / Ica-PDA-FA nanoparticles were dispersed in PBS solution to prepare SiO2 / Ica-PDA-FA nanoparticle suspensions with concentrations of 10, 50, 100 and 200 μg / mL. The PBS solution was used as the control group. A fiber-coupled power-tunable diode laser with a wavelength of 808 nm was used as the NIR light source to irradiate the prepared suspension at powers of 0.5, 1 and 2 W / cm -2 The temperature change curve with time was measured under the conditions of , and the temperature change image of SiO2 / Ica-PDA-FA nanoparticle suspension was collected using a thermal imager. Figure 2 a is the photothermal image of SiO2 / Ica-PDA-FA nanoparticles. Under NIR irradiation, the temperature of PBS did not change significantly, while SiO2 / Ica-PDA-FA nanoparticles could quickly absorb NIR to increase the temperature of the suspension, indicating that SiO2 / Ica-PDA-FA nanoparticles retained the characteristics of PDA and had a good photothermal effect. Figure 2 b shows the temperature of SiO2 / Ica- PDA-FA suspension increases with the increase of NIR irradiation power. The power is set to 2.1 W / cm -2 and 0.5 W / cm -2 After irradiation for 5 min, the temperatures of the suspensions were approximately 53 °C, 45 °C, and 40 °C, respectively. Figure 2 c is at 1 W / cm -2 After 5 min of NIR irradiation, the temperatures of SiO2 / Ica-PDA-FA nanoparticle suspensions with concentrations of 10, 50, 100, and 200 μg / L were 35°C, 37°C, 45°C, and 54°C, respectively, indicating that the temperature of the nanoparticle suspension increased with increasing concentration. -2NIR irradiation of a specific concentration of nanoparticle suspension (≤ 100 μg / L) can control the temperature below 45 °C. In order to achieve good tumor ablation without damaging surrounding tissues, we chose a power of 1 W / cm -2 NIR conducts follow-up tests.
[0071] 2. Photothermal stability experiment
[0072] In order to investigate the photothermal stability of SiO2 / Ica-PDA-FA nanoparticles, 2 mg SiO2 / Ica-PDA-FA nanoparticles were dispersed in 5 mL PBS solution and diluted to prepare a SiO2 / Ica-PDA-FA nanoparticle suspension with a concentration of 100 μg / mL. -2 The nanoparticle suspension was irradiated with NIR light source for 5 min, and the temperature change of SiO2 / Ica-PDA-FA nanoparticle suspension was detected after each irradiation, and the detection was continued for 4 cycles. Figure 2 d. SiO2 / Ica-PDA-FA nanoparticles were continuously irradiated with NIR for 4 times, and the maximum temperature of SiO2 / Ica-PDA-FA nanoparticles did not change, indicating that SiO2 / Ica-PDA-FA nanoparticles did not suffer from photothermal energy loss and had good photothermal stability.
[0073] 3. Drug Release Experiment
[0074] The drug content in the buffer was detected under different environments to investigate the in vitro release of Icaritin from SiO2 / Ica-PDA-FA nanoparticles. 5 mg of nanoparticles were weighed and placed in a dialysis bag, which was placed in a buffer with a pH of 7.4 or 5.5. The mixture was oscillated at 37°C and 1 mL of the release buffer was extracted at specific time intervals. An equal volume of fresh PBS was added and the incubation continued. The Icaritin content in the release solution was determined using a UV spectrophotometer. In addition, the drug release behavior of the nanoparticles under NIR irradiation and in the presence of GSH was studied using the same method. Figure 3The drug release of SiO2 / Ica-PDA-FA nanoparticles was shown in Figure 2. In PBS (pH 7.4) solution, Icaritin was almost not released, indicating that SiO2 / Ica-PDA-FA nanocomplexes have good stability under normal physiological conditions. However, in PBS solution at pH 5.5, the release rate of Icaritin was 25%, indicating that the acidic environment of the tumor can promote the release of Icaritin. Subsequently, GSH was added to the pH 5.5 solution, and the release of Icaritin from SiO2 / Ica-PDA-FA increased to 49% under the dual stimulation of acidity and GSH. To further study the effect of NIR irradiation on the release efficiency, we measured and compared the release efficiency of Icaritin before and after NIR irradiation. Under the conditions of pH 5.5+NIR irradiation, the release rate of Icaritin was 30%. Compared with before irradiation, NIR irradiation can accelerate the release of Icaritin. After pH 5.5+GSH+NIR treatment, the release of Icaritin further increased to 70%, indicating that this dosage form can quickly respond to the tumor cell microenvironment under NIR irradiation and increase the effective dose of intracellular drugs.
[0075] 4. In vitro cell experiments
[0076] (1) Intake experiment
[0077] Colon cancer cells HCT116 were seeded on 24-well plates and incubated in an incubator at 37°C and 5% CO2 for 24 h to ensure cell adhesion. The cells were treated with SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA nanoparticles labeled with Cy5.5 fluorescent molecules for 8 h, and the culture medium was discarded and washed three times with pre-cooled PBS. After fixation with paraformaldehyde for 30 min, the cells were washed with PBS to remove excess paraformaldehyde, and then stained with DAPI at a concentration of 0.5 µg / mL for 10 min in the dark, and then washed with PBS to remove excess dye. The staining results were observed using a laser confocal microscope, and the excitation and emission wavelengths of DAPI were 405 and 462 nm. The cells were collected after treatment with trypsin, and the Cy5.5 fluorescence intensity was detected by flow cytometry. The excitation and emission wavelengths of Cy5.5 were 650 and 670 nm, respectively. Figure 4 a shows that after SiO2 / Ica- PDA-FA nanoparticles were treated, strong red fluorescence appeared in the cells, but after SiO2 / Ica-PDA nanocomplexes were treated, only a small amount of red fluorescence appeared in the cells, indicating that SiO2 / Ica- PDA-FA nanoparticles modified with FA can increase the uptake of HCT116 cells. Figure 4 b is a flow cytometric graph of the uptake of SiO2 / Ica-PDA-FA and SiO2 / Ica-PDA nanoparticles by HCT116 cells. This figure quantitatively analyzes the uptake of SiO2 / Ica-PDA-FA nanoparticles by HCT116 cells. The results show that the red fluorescence intensity in HCT116 cells treated with SiO2 / Ica-PDA-FA nanoparticles is two orders of magnitude higher than that in the blank group, while the red fluorescence in HCT116 cells treated with SiO2 / Ica-PDA nanoparticles is only about 8 times that of the blank group.
[0078] (2) Inhibition of cell proliferation experiment
[0079] Colon cancer cells HCT116 were inoculated in a 96-well culture dish, and 200 μL of culture medium was added. After culturing for 24 h under 5% CO2 and 37°C, the culture medium was removed and culture medium containing free Icaritin, SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA nanoparticles was added. The final concentration of Icaritin in the culture medium was ensured to be 0.1, 0.5, 1, 2, 5, 10, 15, 20, and 25 μg / mL, respectively. Blank PBS was used as the control group, 6 replicate wells were set for the PBS group and the free Icaritin group, and 12 replicate wells were set for the SiO2 / Ica-PDA group and the SiO2 / Ica-PDA-FA group. After 24 h of co-culture, 6 replicate wells of the SiO2 / Ica-PDA group and SiO2 / Ica-PDA-FA group were selected and irradiated with NIR for 5 min. The cells were incubated in the incubator for another 24 h, and the cell proliferation inhibition efficiency was detected by CCK-8.
[0080] Figure 5 a is the inhibition efficiency of HCT116 cells after being treated with nanoparticles of different concentrations. It can be seen from the figure that the IC50 values of free Icaritin and SiO2 / Ica-PDA are 6.1 and 4.9 µg / mL, respectively. SiO2 / Ica-PDA-FA modified with folic acid more significantly inhibits cell activity, with an IC50 value of 4.1 µg / mL. Based on low-temperature photothermal therapy, SiO2 / Ica-PDA+NIR showed a good effect in inhibiting cancer cell proliferation, with an IC50 value of 3.8 µg / mL. In addition, SiO2 / Ica-PDA-FA+NIR combined with targeted low-temperature photothermal therapy showed the best therapeutic effect, with an IC50 value of 1.7 µg / mL.
[0081] (3) Detection of cell apoptosis by flow cytometry
[0082] HCT116 cells were seeded at a certain density in a 6-well culture dish. After the cells adhered to the wall, culture medium containing free Icaritin, SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA was added. After 24 h of co-culture, some SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA groups were irradiated with NIR for 5 min and incubated for another 24 h. After the cells were collected, cell apoptosis was detected by flow cytometry. Figure 5 b is the investigation of SiO2 / Ica-PDA-FA-induced cell apoptosis by Annexin V-FITC / PI staining and flow cytometry. As shown in the figure, in the absence of NIR irradiation, 6.57% of cells in the Icaritin group underwent apoptosis, and 7.32% of cells in the SiO2 / Ica-PDA nanoparticle group were in apoptotic state compared with the control group, indicating that loading Icaritin into nanoparticles can increase cell apoptosis by increasing the amount of nanoparticles phagocytized by HCT116 cells. 27.19% of cells in the SiO2 / Ica-PDA-FA group underwent apoptosis, indicating that FA modification can increase the targeting of SiO2 / Ica-PDA-FA nanoparticles, thereby increasing the apoptosis of HCT116 cells; after NIR irradiation, 23.74% of cells in the SiO2 / Ica-PDA+NIR group and 44.20% of cells in the SiO2 / Ica-PDA-FA+NIR group underwent apoptosis, indicating that SiO2 / Ica-PDA-FA nanoparticles combined with photothermal reaction have a strong inhibitory effect on the proliferation of HCT116 cells.
[0083] (4) Colon cancer cells were inoculated into 24-well culture dishes. After the cells adhered to the wall, culture medium containing free icaritin, SiO2-PDA, SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA was added. After 4 h of co-culture, the cells were irradiated with NIR for 5 min. After the cells were washed with PBS, a mixed solution of 2 μg / mL calcein and 10 μg / mL propidium iodide was added and incubated in the dark for 15 min. The cells were washed three times with PBS to remove excess stain, and the cell live or dead staining was then observed under a fluorescence microscope.
[0084] Figure 6Cell death and viability fluorescence staining and statistics. As shown in the figure, there was no significant change in cell death and viability staining in the PBS group before and after NIR irradiation, indicating that PBS had no photothermal response. After illumination, cells treated with SiO2-PDA nanoparticles partially died, which was due to the photothermal toxicity caused by PDA. After illumination, cells treated with SiO2 / Ica-PDA nanoparticles further partially died, which was due to the cytotoxicity caused by Icaritin and the downregulation of HSP90, and cell ablation caused by low-temperature photothermal. Almost all cells treated with SiO2 / Ica-PDA-FA nanocomplexes died, indicating that FA modification can increase the phagocytosis of tumor cells and further increase the toxicity to tumor cells.
[0085] (5) Colon cancer cell sphere penetration experiment
[0086] The heated 1.5% agarose solution (50 μL, w / v) was quickly added to a 96-well culture dish and naturally cooled and solidified at room temperature. After sterilization by UV irradiation for 2 h, the cells were washed three times with 10% penicillin / streptomycin. HCT116 cells were inoculated in 100 μL 1640 culture medium at a density of 2000 cells per well and cultured for 15 days, with the culture medium replaced every two days. The formed colon cancer cell spheres were incubated with SiO2 / Ica-PDA-FA for 24 h, and the HCT116 cell spheres were washed with PBS after incubation with NIR light. After fixation with 4% paraformaldehyde, the HCT116 cell spheres were transferred to a special culture dish for cell spheres, and the confocal microscope was used to scan layer by layer from the top of the colon cancer cell sphere along the Z axis, with a layer scanning distance of 20-30 μm. The fluorescence photos were superimposed using Image J software, and the images were reconstructed in three dimensions to determine the distribution of nanoparticles in the cell spheres.
[0087] Figure 7a Penetration imaging of solid tumors. Z-stack confocal fluorescence images were captured from the top of the tumor spheroid at intervals of 20-30 µm. When NIR irradiation was applied for 5 s, the red fluorescence inside the colon cancer cell spheroid gradually decreased, with only a small amount of fluorescence at 80 µm, and almost no fluorescence at greater than 80 µm. This indicates that SiO2 / Ica-PDA-FA nanoparticles have a certain degree of permeability when irradiated with NIR for 5 s, but the permeability is poor. Considering that long-term illumination will affect cell activity, we increased the NIR irradiation time to 10 s. The results of Z-stack confocal fluorescence images showed that even at a depth of 140 µm, the center of the colon cancer cell spheroid still had bright fluorescence under 10 s of NIR irradiation. The reason for this may be that the photothermal effect caused the temperature of the cell spheroid microenvironment to increase, thereby increasing the fluidity of the cell membrane. The above results show that NIR irradiation can increase the permeability of SiO2 / Ica-PDA-FA in the cell spheroid, and the permeability increases with the increase of illumination time. The depth of nanoparticle penetration into colon cancer cell spheres was further analyzed by fluorescence statistics. Figure 7 As shown in Figure c, the penetration distance of NIR irradiation for 5 s in colon cancer cell spheres is only 40 μm, while the penetration distance for 10 s can reach 140 μm. The above results more accurately show that NIR irradiation can promote the penetration of nanocomplexes and the longer the illumination time, the better the penetration effect. It is further speculated that NIR can promote SiO2 / Ica-PDA-FA nanoparticles to enter deep into colon cancer tissues, which is crucial to the effect of tumor treatment. Subsequently, the effect of NIR irradiation on the permeability of nanoparticles was quantitatively analyzed. Figure 7 As shown in Figure b, after NIR irradiation for 10 s, the nanoparticles and cell spheroids were co-incubated for another 1 h. The fluorescence intensity of the cell spheroids was 2.5 times that without NIR irradiation. After co-incubation for 2 h, the fluorescence intensity of the cell spheroids irradiated by NIR was 3.1 times that without NIR irradiation. The above results show that NIR irradiation can increase the permeability of nanoparticles in tumor cell spheroids.
[0088] 5. In vivo safety evaluation and anti-tumor activity evaluation
[0089] (1) Distribution of drugs in mice
[0090] A subcutaneous transplanted tumor model of colon cancer was established. After killing mice at a specific time point, 300 mg of heart, liver, spleen, lung, kidney and tumor tissues were weighed and placed in a mortar and ground with 1.2 mL of anhydrous ethanol. After making a homogenate, 1.5 mL of anhydrous ethanol was added and shaken and centrifuged for 5 min (3500 rpm) to collect the supernatant. After dilution, the precipitated protein was detected by high performance liquid chromatography to detect the content of Icaritin in various tissues. Normal mouse organ homogenates were taken to establish the Icaritin standard curves of various tissues, and the Icaritin content was calculated based on the standard curves.
[0091] Figure 8 In order to verify the targeting effect of nanoparticles in vivo, we used high performance liquid chromatography to detect the distribution and retention of Icaritin in major organs at different time points in vivo. As shown in the figure, within 24 hours of administration, the drug was mainly distributed in the liver, spleen, kidney and tumor tissue, indicating that the drug and nanoparticles were mainly eliminated from the body through liver, spleen and kidney metabolism. Compared with other treatment groups, the concentration of Icaritin in the SiO2 / Ica-PDA-FA+NIR group gradually increased in tumor tissue from the 1st to the 8th hour after administration, which was due to the fact that SiO2 / Ica-PDA-FA+NIR nanoparticles could effectively target tumor tissues, and NIR irradiation was conducive to promoting the penetration and retention of nanoparticles in the tumor site, thereby better exerting the anti-tumor effect. In addition, free Icaritin showed a low blood drug concentration, which was almost undetectable after 5 hours of administration, indicating that it was quickly cleared from the body, while the drug concentrations of SiO2 / Ica-PDA and SiO2 / Ica-PDA-FA groups at 24 hours were still 16% and 25%. The above results indicate that SiO2 / Ica-PDA-FA nanoparticles can prolong the blood circulation time of Icaritin.
[0092] (2) In vivo safety evaluation
[0093] After 24 hours of treatment, the blood of the mice was collected and centrifuged at 4°C to collect serum for testing of AST, ALP, ALT, BUN and Creatinine. After 21 days of treatment, fresh tissues such as heart, liver, spleen, lung and kidney of mice in each group were collected for H&E staining. Fig. 9 To evaluate the in vivo safety of nanoparticles. Through H&E staining of major organ tissue sections, Fig. 9a is the H&E staining of the heart, liver, spleen, lung, and kidney tissues of mice after nanoparticle treatment. The results are shown in the figure. No obvious tissue damage was observed after treatment with the SiO2 / Ica-PDA-FA nanoparticle group. In addition, blood biochemistry results of aspartate aminotransferase AST, alanine aminotransferase ALT, alkaline phosphatase ALP, blood urea nitrogen BUN, and creatinine CRE are often used to assess the degree of liver and kidney damage. In the blood biochemistry results of hepatocyte damage, the ALT, AST, and ALP values will increase, and kidney damage will cause changes in the values of BUN and CRE. Fig. 9 As shown in b, there was no significant change in AST, ALT, ALP, BUN and CRE of mice treated with SiO2 / Ica-PDA-FA nanoparticles compared with those in the PBS control group. The results showed that SiO2 / Ica-PDA-FA nanoparticles did not cause obvious liver and kidney toxicity after treatment.
[0094] (3) Evaluation of anti-tumor activity
[0095] A subcutaneous transplanted tumor model of colon cancer was established. The mice with successful modeling were randomly divided into 6 groups, with 6 mice in each group. After grouping, the same dose of Icaritin (10 mg / kg) was injected into the tail vein of free Icaritin (6 mice), SiO2 / Ica-PDA (12 mice) and SiO2 / Ica-PDA-FA (12 mice). The PBS group (6 mice) was used as the control group. 24 h and 48 h after administration, the SiO2 / Ica-PDA group (6 mice) and the SiO2 / Ica-PDA-FA group (6 mice) were respectively given 808 nm NIR (the power density of the laser was 1 W / cm -2 ) light, and the spot area was adjusted to completely cover the tumor during illumination. After NIR irradiation, a thermal imager was used to record temperature changes, and an infrared camera was used to collect photothermal images of mice within 120 seconds. The weight of mice and the long and short axes of tumors were recorded every two days after the start of administration, and the changes in tumor volume were calculated. The diet, spirit, activity and other living conditions of mice were observed. After 21 days of treatment, the mice were painlessly killed, and the changes in tumor volume and weight of mice were observed and measured. Tumor tissues were collected, embedded, and sliced for Ki-67 and Caspase 3 immunohistochemical staining.
[0096] Fig.10The photothermal effect of SiO2 / Ica-PDA-FA nanoparticles in mice. 24 h after intravenous administration, the photothermal images of mice within 120 s of NIR irradiation were collected with an infrared camera. As shown in the figure, with the extension of NIR irradiation time, the tumor site in the PBS control group appeared bright yellow, while the SiO2 / Ica-PDA-FA group showed red, and the local temperature of the tumor reached 43.2 ± 2.5℃, with obvious photothermal effect. The above results show that FA modification increases the enrichment of nanoparticles in the tumor site. Fig.11 The therapeutic effect of nanoparticles. Fig.11 a shows the changes in the appearance of subcutaneous tumors in tumor-bearing mice after nanoparticle treatment. The volume of subcutaneous tumor tissue in mice treated with SiO2 / Ica-PDA-FA group is smaller than that in SiO2 / Ica-PDA group, indicating that the surface modification of FA in nanoparticles improves the tumor targeting of nanoparticles and has better anti-tumor effect. The volume of subcutaneous tumor tissue in mice treated with SiO2 / Ica-PDA-FA+NIR group is smaller than that in SiO2 / Ica-PDA-FA group, indicating that SiO2 / Ica-PDA-FA nanocomplex combined with NIR irradiation can increase the anti-tumor effect of nanoparticles. Mice were killed after 21 days of treatment, and tumor tissues were removed to analyze the treatment effect. The in vivo therapeutic effect of SiO2 / Ica-PDA-FA nanoparticles was investigated by monitoring the tumor volume in mice. Figure 11b is a representative photo of the peeled tumor tissue. As shown in the figure, the tumor volumes of each group after treatment are PBS > Icaritin > SiO2 / Ica- PDA > SiO2 / Ica-PDA+NIR > SiO2 / Ica-PDA-FA+NIR. Compared with other treatment groups, the tumor volume of the SiO2 / Ica-PDA-FA+NIR group is the smallest, indicating that the nanoparticles combined with low-temperature photothermal therapy have a good tumor inhibitory effect. Fig.11cd, the tumor size after free Icaritin treatment was slightly smaller than that of the PBS control group, and the tumor growth trend during the entire treatment period was consistent with that of the PBS control group, indicating that Icaritin has a certain inhibitory effect on colon cancer, but the effect is limited. After SiO2 / Ica-PDA nanoparticle treatment, the tumor size was smaller than that of free Icaritin, and the tumor growth curve began to slow down during the entire treatment period, which may be due to the retention effect of SiO2 / Ica-PDA nanoparticles, which increased the concentration of SiO2 / Ica-PDA nanoparticles in the tumor site. After treatment with SiO2 / Ica-PDA-FA group, the tumor size was reduced compared with that of SiO2 / Ica-PDA group; the tumor tissue size treated with SiO2 / Ica-PDA+NIR group was significantly reduced compared with that of SiO2 / Ica-PDA-FA treatment group, and the tumor growth curve slowed down significantly during the entire treatment period, indicating that photothermal therapy and Icaritin have a certain synergistic effect. During the entire treatment period, the tumor in the SiO2 / Ica-PDA-FA+NIR treatment group showed no obvious growth, and no obvious nodules were observed at the tumor site of the mice after the treatment. The experimental results showed that the SiO2 / Ica-PDA-FA+NIR treatment group showed better tumor inhibition. Fig.11 e is the change in mouse body weight during the entire treatment period. As the tumor grew, the weight of mice in the PBS, free Icaritin, SiO2 / Ica-PDA, and SiO2 / Ica-PDA+NIR treatment groups first increased and then decreased. The weight of mice in the SiO2 / Ica-PDA-FA and SiO2 / Ica-PDA-FA+NIR treatment groups increased slightly during the entire treatment period, indicating that SiO2 / Ica-PDA-FA nanoparticles combined with NIR irradiation had no obvious toxic side effects and had no significant effect on mouse body weight. Fig.11 f is the survival curve during the entire treatment period. As shown in the figure, the median lethal time of the PBS and Icaritin groups was the 10th day and the 13th day, while the survival time of the mice was prolonged after treatment with SiO2 / Ica-PDA, SiO2 / Ica-PDA-FA, and SiO2 / Ica-PDA+NIR groups. At the end of the experiment, the survival rate of the SiO2 / Ica-PDA-FA+NIR treatment group was 75%. Fig.11g is H&E and immunohistochemical staining of tumor tissue. In the H&E results, the tumor tissue treated with PBS group showed higher survival rate, obvious nucleolar lysis and stronger malignancy. After Icaritin treatment, necrotic areas appeared in the tumor tissue. After treatment with SiO2 / Ica-PDA, SiO2 / Ica-PDA+NIR and SiO2 / Ica- PDA-FA groups, the necrotic areas became larger, and the tumor cells showed obvious vacuolar degeneration; while after treatment with SiO2 / Ica- PDA-FA+NIR nanoparticles group, a higher degree of cell necrosis was shown, and more condensation and disappearance of nucleoplasm were observed. Ki-67 is a macromolecular protein derived from a component of the nuclear matrix and chromosome scaffold that can provide a place for DNA replication. Ki-67 is a marker representing the level of cell proliferation, which is used to quickly and reliably respond to the proliferation of malignant tumors. Overexpression and activation of cysteine protease-3 (Caspase 3) induces cell apoptosis and is often used to mark apoptotic cells. In the immunohistochemistry results of Ki-67 and caspase 3, the PBS group showed high cell proliferation. After treatment with SiO2 / Ica-PDA, SiO2 / Ica- PDA+NIR and SiO2 / Ica-PDA-FA nanoparticle groups, the tumor cell proliferation levels were successively downregulated, and apoptotic cells gradually increased. The results showed that after treatment with SiO2 / Ica-PDA-FA+NIR nanoparticle group, cell proliferation was significantly inhibited and cell apoptosis was significantly increased, showing a good anti-tumor effect in vivo.
[0097] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing SiO2 / Ica-PDA-FA multifunctional nanoparticles, characterized in that: The preparation method comprises: dispersing silicon dioxide in a dispersion liquid to form a suspension; After adding icariin to the suspension, the reaction was stirred at room temperature and then centrifuged and dried to obtain SiO2 / Ica nanoparticles; the mass ratio of silicon dioxide to icariin was 4-6:1; Dopamine hydrochloride is dispersed in a solvent to form a dopamine hydrochloride solution; The dopamine hydrochloride solution and SiO2 / Ica nanoparticles were mixed and reacted at room temperature, and then centrifuged and dried to obtain SiO2 / Ica-PDA nanoparticles with a core-shell structure; the mass ratio of dopamine hydrochloride to SiO2 / Ica nanoparticles was 0.8-1.2:1; dissolving NH2-PEG-FA in a buffer solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to obtain an NH2-PEG-FA solution; SiO2 / Ica-PDA nanoparticles are dispersed in the dispersion to form a SiO2 / Ica-PDA suspension; The NH2-PEG-FA solution is added dropwise to the SiO2 / Ica-PDA suspension for reaction, and after the reaction is completed, the SiO2 / Ica-PDA-FA multifunctional nanoparticles are obtained by centrifugation and washing; The mass ratio of the NH2-PEG-FA, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide and SiO2 / Ica-PDA nanoparticles is 0.7-1.2:1.8-2.2:0.8-1.5:5.5-6.
3.
2. The method for preparing SiO2 / Ica-PDA-FA multifunctional nanoparticles according to claim 1, characterized in that: The NH2-PEG-FA is prepared by the following steps: dissolving the NH2-PEG-NH2 polymer in a NaHCO3 solution to form an NH2-PEG-NH2 solution; (Boc)2O is dissolved in dioxane solution to form (Boc)2O solution; NH2-PEG-NH2 polymer, NaHCO 3、 The mass ratio of (Boc)2O and dioxane is: 1.5~2.2:0.253:0.206:62.04; Add (Boc)2O solution to NH2-PEG-NH2 solution under ice bath condition, react at room temperature after adding, adjust pH value to 7-8 after reaction, extract after rotary evaporation to obtain BOC-PEG-NH2; add solvent to BOC-PEG-NH2 to obtain BOC-PEG-NH2 solution; Dissolving folic acid in a buffer solution containing 1-ethyl-(3-dimethylaminopropylcarbodiimide) and N-hydroxysuccinimide to form a folic acid solution; the mass ratio of folic acid, 1-ethyl-(3-dimethylaminopropylcarbodiimide) and N-hydroxysuccinimide is 0.8-1.2:2:1.2; The BOC-PEG-NH2 solution was added dropwise to the folic acid solution for reaction at room temperature. After the reaction was completed, BOC-PEG-FA was obtained by rotary evaporation. BOC-PEG-FA was dissolved in anhydrous dichloromethane, and trifluoroacetic acid was added to react at room temperature. After the reaction was completed, the NH2-PEG-FA was obtained by rotary evaporation, ether precipitation and vacuum drying; the mass ratio of BOC-PEG-FA, anhydrous dichloromethane and trifluoroacetic acid was 0.8~1.3:13.25:5.3725.
3. The method for preparing SiO2 / Ica-PDA-FA multifunctional nanoparticles according to claim 1, characterized in that: The silicon dioxide is prepared by the following steps: dissolving hexadecyltrimethylammonium bromide in a solvent containing aqueous ammonia to form a mixed solution; The mixed solution is added into a mixed solution formed by ethyl orthosilicate and bis-[3-(triethoxy)silylpropyl]tetrasulfide, and after the reaction is completed, a white precipitate is obtained by centrifugation; The mass ratio of hexadecyltrimethylammonium bromide to ethyl orthosilicate is 20~35mg:1.5~2.0ml; The volume ratio of ethyl orthosilicate to bis-[3-(triethoxy)silylpropyl]tetrasulfide is 0.7~1.2:
1.
4. The method for preparing SiO2 / Ica-PDA-FA multifunctional nanoparticles according to claim 3, characterized in that: The white precipitate is purified by acidic ethanol reflux method.
5. The method for preparing SiO2 / Ica-PDA-FA multifunctional nanoparticles according to claim 3, characterized in that: Disperse the white precipitate in acidic ethanol solution and reflux for 7 to 9 hours.
6. The method for preparing SiO2 / Ica-PDA-FA multifunctional nanoparticles according to claim 3, characterized in that: The temperature of the mixed solution during the formation process is 75-82°C.
7. SiO2 / Ica-PDA-FA multifunctional nanoparticles prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the SiO2 / Ica-PDA-FA multifunctional nanoparticles according to claim 7 in the preparation of tumor therapeutic drugs.
9. The use according to claim 8, wherein the tumor comprises rectal cancer.
Citation Information
Patent Citations
Method for preparing folate molecular targeted magnetic nanometer medicine carrier and targeting gene medicine
CN102145177A
Folate-polyethylene glycol-polylactic acid segmented copolymer micelle encapsulated with hydrophobic anticancer drug and preparation method of segmented copolymer micelle
CN103520731A
Folic acid and polydopamine modified tumor targeted mesoporous silica nanoparticle and preparation method and application thereof
CN106806343A
Binary drug loading nanoparticle with pH response and tumor targeting effect as well as preparation method and application thereof
CN107233577A
Composition for delivering physiologically active ingredients into blood vessel
US20200163885A1
Cited By
Drug delivery system and preparation method and application thereof
CN119925293A